23Na MRI Depicts Early Changes in Ion Homeostasis in Skeletal Muscle Tissue of Patients With Duchenne Muscular Dystrophy - Gerhalter, Teresa; Gast, Lena; Marty, Benjamin; Martin, Jan; Trollmann, Regina; Schüssler, Stephanie; Roemer, Frank; Uder, Michael; Schröder, Rolf; Carlier, Pierre G.; Nagel, Armin Michael; Laun, Frederik Bernd (Journal of Magnetic Resonance Imaging, 2019)
BACKGROUND: Duchenne muscular dystrophy (DMD) is a hereditary neuromuscular disease leading to progressive muscle wasting. Since there is a need for MRI variables that serve as early sensitive indicators of response to treatment, several quantitative MRI methods have been suggested for disease monitoring. PURPOSE: To evaluate the potential of sodium (23 Na) and proton (1 H) MRI methods to assess early pathological changes in skeletal muscle of DMD. STUDY TYPE: Prospective clinical study. POPULATION: 23 Na and 1 H MRI of the right leg were performed in 13 patients with DMD (age 7.8 ± 2.4) and 14 healthy boys (age 9.5 ± 2.2). FIELD STRENGTH/SEQUENCE: 3 T including a multiecho-spin-echo sequence, diffusion-weighted sequences, 1 H spectroscopy, 3-pt Dixon, and 23 Na ultrashort echo time sequences. ASSESSMENT: We obtained water T2 maps, fat fraction (FF), pH, and diffusion properties of the skeletal muscle tissue. Moreover, total tissue sodium concentration (TSC) was calculated from the 23 Na sequence. Intracellular-weighted 23 Na signal (ICwS) was derived from 23 Na inversion-recovery imaging. STATISTICAL TESTS: Results from DMD patients and controls were compared using Wilcoxon rank-sum tests and repeated analysis of variance (ANOVA). Spearman-rank correlations and area under the curve (AUC) were calculated to assess the performance of the different MRI methods to distinguish dystrophic from healthy muscle tissue. RESULTS: FF, water T2 , and pH were higher in DMD patients (0.07 ± 0.03, 39.4 ± 0.8 msec, 7.06 ± 0.03, all P < 0.05) than in controls (0.02 ± 0.01, 36.0 ± 0.4 msec, 7.03 ± 0.02). No difference was observed in diffusion properties. TSC (26.0 ± 1.3 mM, P < 0.05) and ICwS (0.69 ± 0.05 a.u., P < 0.05) were elevated in DMD (controls: 16.5 ± 1.3 mM and 0.47 ± 0.04 a.u.). The ICwS was frequently abnormal in DMD even when water T2 , FF, and pH were in the normal range. 23 Na MRI showed higher AUC values in comparison to the 1 H methods. DATA CONCLUSION: Sodium anomalies were regularly observed in patients with DMD compared with controls, and were present even in absence of fatty degenerative changes and water T2 increases. LEVEL OF EVIDENCE: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;50:1103-1113.
CRIS-Team Scopus Importer:2019-09-20
Keywords: Duchenne muscular dystrophy; proton MRI; skeletal muscle; sodium MRI

23Na MRI of human skeletal muscle using long inversion recovery pulses - Wilferth, Tobias; Gast, Lena; Stobbe, Robert W.; Beaulieu, Christian; Hensel, Bernhard; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance Imaging, 2019)
23Na inversion recovery (IR) imaging allows for a weighting toward intracellular sodium in the human calf muscle and thus enables an improved analysis of pathophysiological changes of the muscular ion homeostasis. However, sodium signal-to-noise ratio (SNR) is low, especially when using IR sequences. 23Na has a nuclear spin of 3/2 and therefore experiences a strong electrical quadrupolar interaction. This results in very short relaxation times as well as in possible residual quadrupolar splitting. Consequently, relaxation effects during a radiofrequency pulse can no longer be neglected and even allow for increasing SNR as has previously been shown for human brain and knee. The aim of this work was to increase the SNR in 23Na IR imaging of the human calf muscle by using long inversion pulses instead of the usually applied short pulses. First, the influence of the inversion pulse length (1 to 20 ms) on the SNR as well as on image contrast was simulated for different model environments and verified by phantom measurements. Depending on the model environment (agarose 4% and 8%, xanthan 2% and 3%), SNR values increased by a factor of 1.15 up to 1.35, while NaCl solution was successfully suppressed. Thus, image contrast between the non-suppressed model compartments changes with IR pulse length. Finally, in vivo measurements of the human calf muscle of ten healthy volunteers were conducted at 3 Tesla. On average, a 1.4-fold increase in SNR could be achieved by increasing the inversion pulse length from 1 ms to 20 ms, leaving all other parameters – including the scan time – constant. This enables 23Na IR MRI with improved spatial resolution or reduced acquisition time.
CRIS-Team Scopus Importer:2019-10-22
Keywords: B; Human skeletal muscle; Intracellular weighting; Inversion recovery; Long inversion pulses; Sodium (

Assessing muscle-specific potassium concentrations in human lower leg using potassium magnetic resonance imaging - Gast, Lena; Baier, Laura-Marie; Chaudry, Oliver; Meixner, Christian; Müller, Max; Engelke, Klaus; Uder, Michael; Heiß, Rafael; Nagel, Armin Michael (NMR in Biomedicine, 2022)
Noninvasively assessing tissue potassium concentrations (TPCs) using potassium magnetic resonance imaging (39K MRI) could give valuable information on physiological processes connected to various pathologies. However, because of inherently low 39K MR image resolution and strong signal blurring, a reliable measurement of the TPC is challenging. The aim of this work was to investigate the feasibility of a muscle-specific TPC determination with a focus on the influence of a varying residual quadrupolar interaction in human lower leg muscles. The quantification accuracy of a muscle-specific TPC determination was first assessed using simulated 39K MRI data. In vivo 39K and corresponding sodium (23Na) MRI data of healthy lower leg muscles (n = 14, seven females) were acquired on a 7-T MR system using a double-resonant 23Na/39K birdcage Tx/Rx RF coil. Additional 1H MR images were acquired on a 3-T MR system and used for tissue segmentation. Quantification of TPC was performed after a region-based partial volume correction (PVC) using five external reference phantoms. Simulations not only underlined the importance of PVC for correctly assessing muscle-specific TPC values, but also revealed the strong impact of a varying residual quadrupolar interaction between different muscle regions on the measured TPC. Using 39K T2* decay curves, we found significantly higher residual quadrupolar interaction in tibialis anterior muscle (TA; ωq = 194 ± 28 Hz) compared with gastrocnemius muscle (medial/lateral head, GM/GL; ωq = 151 ± 25 Hz) and soleus muscle (SOL; ωq = 102 ± 32 Hz). If considered in the PVC, TPC in individual muscles was similar (TPC = 98 ± 11/96 ± 14/99 ± 8/100 ± 12 mM in GM/GL/SOL/TA). Comparison with tissue sodium concentrations suggested that residual quadrupolar interactions might also influence the 23Na MRI signal of lower leg muscles. A TPC determination of individual lower leg muscles is feasible and can therefore be applied in future studies. Considering a varying residual quadrupolar interaction for PVC of 39K MRI data is essential to reliably assess potassium concentrations in individual muscles.
CRIS-Team Scopus Importer:2022-09-16
Keywords: 7 T; muscle MRI; potassium (; sodium (; tissue potassium concentration; tissue sodium concentration; ultrahigh field strengths

Assessing the variability of 23Na MRI in skeletal muscle tissue: Reproducibility and repeatability of tissue sodium concentration measurements in the lower leg at 3 T - Gerhalter, Teresa; Gast, Lena; Marty, Benjamin; Uder, Michael; Carlier, Pierre G.; Nagel, Armin Michael (NMR in Biomedicine, 2020)
The goal of this study was to evaluate the reproducibility and repeatability of tissue sodium concentration (TSC) measurements using 23Na MRI in skeletal muscle tissue. 23Na MRI was performed at 3 T on the right lower leg of eight healthy volunteers (aged 28 ± 4 years). The examinations were repeated at the same site after 22 weeks to assess the variability over a medium-term period. Additionally, they were scanned at a second site shortly before or shortly after the first visit (within 3 weeks) to evaluate the inter-site reproducibility. Moreover, we analysed the effect of B0 correction on the variability. Coefficients of variations (CVs) from mean TSC values as well as Bland–Altman plots were used to assess intra-site repeatability and inter-site reproducibility. In phantom measurements, the B0 correction improved the quantitative accuracy. We observed differences of up to 4.9 mmol/L between the first and second visit and a difference of up to 3.7 mmol/L between the two different sites. The CV for the medium-term repeatability was 15% and the reproducibility CV was 9%. The Bland–Altman plots indicated high agreement between the visits in all muscle regions. The systematic bias of −0.68 mmol/L between site X and Y (P = 0.03) was slightly reduced to −0.64 mmol/L after B0 correction (P = 0.04). This work shows that TSC measurements in healthy skeletal muscle tissue can be performed with good repeatability and reproducibility, which is of importance for future longitudinal or multicentre studies.
CRIS-Team Scopus Importer:2020-03-17
Keywords: quantification; repeatability; reproducibility; skeletal muscle tissue; sodium MRI; total tissue sodium content

Combined imaging of potassium and sodium in human skeletal muscle tissue at 7 T - Gast, Lena; Volker, Stefanie; Utzschneider, Matthias; Linz, Peter; Wilferth, Tobias; Müller, Max; Kopp, Christoph; Hensel, Bernhard; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2020)
Purpose: To validate the feasibility of quantitative combined potassium (39K) and sodium (23Na) MRI in human calf muscle tissue, as well as to evaluate the reproducibility of the apparent tissue potassium concentration (aTPC) and apparent tissue sodium concentration (aTSC) determination in healthy muscle tissue. Methods: Quantitative 23Na and 39K MRI acquisition protocols were implemented on a 7 T MR system. A double-resonant 23Na/39K birdcage RF coil was used. Measurements of human lower leg were performed in a total acquisition time of TANa = 10:54 min/TAK = 8:06 min and using a nominal spatial resolution of 2.5 × 2.5 × 15 mm3/7.5 × 7.5 × 30 mm3 for 23Na/39K MRI. Two aTSC and aTPC examinations in muscle tissue were performed during the same day on 10 healthy subjects. Results: The proposed acquisition and postprocessing workflow for 23Na and 39K MRI data sets provided reproducible aTSC and aTPC measurements. In human calf muscle tissue, the coefficient of variation between scan and re-scan was 5.7% for both aTSC and aTPC determination. Overall, mean values of aTSC = (17 ± 1) mM and aTPC = (85 ± 5) mM were measured. Moreover, for 39K in calf muscle tissue, (Formula presented.) components of (Formula presented.) = (1.2 ± 0.2) ms and (Formula presented.) = (7.9 ± 0.9) ms, as well as a residual quadrupolar interaction of (Formula presented.) = (143 ± 17) Hz, were determined. The fraction of the fast component was f = (58 ± 4)%. Conclusion: Using the presented measurement and postprocessing approach, a reproducible aTSC and aTPC determination using 23Na and 39K MRI at 7 T in human skeletal muscle tissue is feasible in clinically acceptable acquisition durations.
CRIS-Team Scopus Importer:2020-09-11
Keywords: 7 T; potassium MRI; sodium MRI; tissue potassium concentration; tissue sodium concentration; ultrahigh field strengths

Correction to: Accelerated quantification of tissue sodium concentration in skeletal muscle tissue: quantitative capability of dictionary learning compressed sensing (Magnetic Resonance Materials in Physics, Biology and Medicine, (2020), 10.1007/s10334-019-00819-2) - Utzschneider, Matthias; Behl, Nicolas G.R.; Lachner, Sebastian; Gast, Lena; Maier, Andreas; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance Materials in Physics Biology and Medicine, 2020)
The original version of this article unfortunately contained a mistake. Title was incorrect. The corrected title is given below. Accelerated quantification of tissue sodium concentration in skeletal muscle tissue: quantitative capability of dictionary learning compressed sensing. The original article has been corrected.
CRIS-Team Scopus Importer:2020-02-25

Double quantum filtered 23 Na MRI with magic angle excitation of human skeletal muscle in the presence of B0 and B1 inhomogeneities - Gast, Lena; Gerhalter, Teresa; Hensel, Bernhard; Uder, Michael; Nagel, Armin Michael (NMR in Biomedicine, 2018)
Double quantum filtered 23 Na MRI with magic angle excitation (DQF-MA) can be used to selectively detect sodium ions located within anisotropic structures such as muscle fibers. It might therefore be a promising tool to analyze the microscopic environment of sodium ions, for example in the context of osmotically neutral sodium retention. However, DQF-MA imaging is challenging due to various signal dependences, on both measurement parameters and external influences. The aim of this work was to examine how B0 in combination with B1 inhomogeneities alter the DQF-MA signal intensity. We showed that, in the presence of B0 inhomogeneities, flip angle schemes with only one 54.7° pulse can be favorable compared with the classical 90°-54.7°-54.7° scheme. DQF-MA images of the human lower leg were acquired at B0 = 3 T with a nominal spatial resolution of 12 × 12 × 36 mm3 within an acquisition time of TAcq < 10 min, and compared with spin density weighted (DW), as well as triple quantum filtration (TQF) 23 Na images. We found mean normalized signal-to-noise ratios of TQF/DW = 13.7 ± 2.3% (tibialis anterior), 11.9 ± 2.3% (soleus) and 11.4 ± 2.2% (gastrocnemius medialis), as well as DQF-MA/DW = 4.7 ± 1.1% (tibialis anterior), 3.3 ± 0.73% (soleus) and 3.4 ± 0.6% (gastrocnemius medialis). These ratios might serve as additional measures in future clinical studies of sodium retention within human skeletal muscle. However, the influence of B0 and B1 inhomogeneities should be considered when interpreting DQF-MA images.
EVALuna2:36106

Imaging of muscle injuries in sports medicine - Heiß, Rafael; Janka, Rolf Matthias; Uder, Michael; Hotfiel, Thilo; Gast, Lena; Nagel, Armin Michael; Roemer, Frank (Die Radiologie, 2023)
Background: Early diagnosis of muscle injuries is indispensable in order to initiate appropriate treatment and to facilitate optimal healing.Purpose: The aim of this review is to provide an update on imaging of muscle injuries in sports medicine with a focus on ultrasound and magnetic resonance imaging (MRI) and to present experimental approaches in addition to routine diagnostic procedures.Materials and methods: A PubMed literature search for the years 2012-2022 using the following keywords was performed: muscle, muscle injury, muscle imaging, muscle injury classification, delayed onset muscle soreness, ultrasound, MRI, sodium MRI, potassium MRI, ultra-high-field MRI, injuries of athletes.Results: Imaging is crucial to confirm and assess the extent of sports-related muscle injuries and may help establishing treatment decisions, which directly affect the prognosis. This is of importance when the diagnosis or grade of injury is unclear, when recovery is taking longer than expected, and when interventional or surgical management may be necessary. In addition to established methods such as B-mode ultrasound and H-1-MRI, individual studies show promising approaches to further improve the imaging of muscle injuries in the future. Prior to the integration of contrast-enhanced ultrasound and X-nuclei into clinical routine, additional studies are needed to validate these techniques further.Conclusion: B-mode ultrasound represents an easily available, cost-effective modality for the initial diagnosis of muscle injuries. MRI is still considered the reference standard and enables an accurate morphological assessment of the extent of the injury. There are still no imaging approaches available for the objective determination of the optimal point of return to play.
CRIS-Team WoS Importer:2023-03-24

Interleaved 23Na/1H MRI of the human heart at 7 T using a combined 23Na/1H coil setup and 1H parallel transmission - Ruck, Laurent; Egger, Nico; Wilferth, Tobias; Schirmer, Judith; Gast, Lena; Nagelstraßer, Sophia; Wildenberg, Saskia; Bitz, Andreas; Lanz, Titus; Platt, Tanja; Konstandin, Simon; Kopp, Christoph; et al. (Magnetic Resonance in Medicine, 2025)
Purpose: To evaluate the feasibility of interleaved 23Na/1H cardiac MRI at 7 T using 1H parallel transmission (pTx) pulses. Methods: A combined setup consisting of a 23Na volume coil and two 1H transceiver arrays was employed and the transmit and receive characteristics were compared in vitro with those of the uncombined radiofrequency coils. Furthermore, the implemented interleaved 23Na/1H pTx sequence was validated in phantom measurements and applied to four healthy subjects. For the latter, three customized 1H excitation pulses (universal and individual phase shims (UPS/IPS) and individual 4kT pulses (4kT)) were employed in the interleaved 23Na/1H pTx sequence and compared with the vendor-provided default cardiac phase shim (DPS). Results: Combining both coils resulted in a reduction of the mean 23Na transmit field (B1+) efficiency and 23Na signal-to-noise ratio by 18.9% and 15.4% for the combined setup, whereas the 1H B1+ efficiency was less influenced (−4.7%). Compared with single-nuclear acquisitions, interleaved dual-nuclear 23Na/1H MRI showed negligible influence on 23Na and 1H image quality. For all three customized 1H pTx pulses the B1+ homogeneity was improved (coefficients of variation: CVUPS = 0.30, CVIPS = 0.23, CV4kT = 0.15) and no 1H signal dropouts occurred compared with the vendor-provided default phase shim (CVDPS = 0.37). Conclusion: The incorporation of customized 1H pTx pulses in an interleaved 23Na/1H sequence scheme was successfully demonstrated at 7 T and improvements of the 1H B1+ homogeneity within the heart were shown. Combining interleaved 23Na/1H MRI with 1H pTx is an important tool to enable robust quantification of myocardial tissue sodium concentrations at 7 T within clinically acceptable acquisition times.
CRIS-Team Scopus Importer:2025-04-01
Keywords: 7 Tesla; cardiac sodium (; interleaved acquisition; parallel transmission (pTx)

Localized B-0 shimming based on Na-23 MRI at 7 T - Gast, Lena; Henning, Anke; Hensel, Bernhard; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2019)
Purpose To validate the feasibility of localized B-0 shimming based on B-0 maps acquired with sodium (Na-23) MRI. Methods A localized B-0 shimming routine based on a constrained regularized algorithm in combination with Na-23 MRI data acquired with a 3D density-adapted radial readout scheme was implemented on a 7T MR system. Measurements were performed using a dual-tuned Na-23/H-1 head coil. The quality of B-0 maps reconstructed from Na-23 images and the resulting shim values was examined depending on the acquisition duration between 10 minutes and 15 seconds to examine clinical applicability. The B-0 shimming based on Na-23 B-0 maps was performed both for phantom and human head of 6 healthy volunteers, and the resulting B-0 homogeneity was compared with the vendor-provided H-1 MRI-based gradient-echo brain shimming routine. Results The proposed Na-23 MRI-based shimming routine showed a reduction in B-0 variation comparable to the vendor-provided shim both in phantom and in vivo measurements. Within the examined multicompartment phantom, the B-0 variations could be reduced by up to 77% using the Na-23 MRI-based shim. In human head, B-0 variations were reduced by approximately 50% using an acquisition time of 15 seconds for the Na-23 B-0 maps and only 1 iteration of B-0 shimming. Conclusion The Na-23 MRI-based localized B-0 shimming is possible at 7 T within clinically acceptable acquisition durations (< 1 minute). It was shown that using the proposed Na-23 MRI-based shimming approach, the Na-23 image quality at ultrahigh field strength can be strongly improved.
CRIS-Team WoS Importer:2019-10-22

Magnetic resonance imaging techniques for the quantitative analysis of skeletal muscle: State of the art. - Engelke, Klaus; Chaudry, Oliver; Gast, Lena; Eldib, Mootaz AB; Wang, Ling; Laredo, Jean Denis; Schett, Georg; Nagel, Armin Michael (Journal of Orthopaedic Translation, 2023)
BACKGROUND: Magnetic resonance imaging (MRI) is the dominant 3D imaging modality to quantify muscle properties in skeletal muscle disorders, in inherited and acquired muscle diseases, and in sarcopenia, in cachexia and frailty. METHODS: This review covers T1 weighted and Dixon sequences, introduces T2 mapping, diffusion tensor imaging (DTI) and non-proton MRI. Technical concepts, strengths, limitations and translational aspects of these techniques are discussed in detail. Examples of clinical applications are outlined. For comparison 31P-and 13C-MR Spectroscopy are also addressed. RESULTS: MRI technology provides a rich toolset to assess muscle deterioration. In addition to classical measures such as muscle atrophy using T1 weighted imaging and fat infiltration using Dixon sequences, parameters characterizing inflammation from T2 maps, tissue sodium using non-proton MRI techniques or concentration or fiber architecture using diffusion tensor imaging may be useful for an even earlier diagnosis of the impairment of muscle quality. CONCLUSION: Quantitative MRI provides new options for muscle research and clinical applications. Current limitations that also impair its more widespread use in clinical trials are lack of standardization, ambiguity of image segmentation and analysis approaches, a multitude of outcome parameters without a clear strategy which ones to use and the lack of normal data.
EVALuna2:540329

Motion-corrected 23Na MRI of the human brain using interleaved 1H 3D navigator images - Wilferth, Tobias; Müller, Max; Gast, Lena; Ruck, Laurent; Meyerspeer, Martin; Kolkovsky, Alfredo L. Lopez; Uder, Michael; Dörfler, Arnd; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2022)
Purpose: To evaluate the feasibility of motion correction for sodium (23Na) MRI based on interleaved acquired 3D proton (1H) navigator images. Methods: A 3D radial density-adapted sequence for interleaved 23Na/1H MRI was implemented on a 7 Tesla whole-body MRI system. The 1H data obtained during the 23Na acquisition were used to reconstruct 140 navigator image volumes with a nominal spatial resolution of (2.5 mm)3 and a temporal resolution of 6 s. The motion information received from co-registration was then used to correct the 23Na image dataset, which also had a nominal spatial resolution of (2.5 mm)3. The approach was evaluated on six healthy volunteers, whose motion during the scans had different intensities and characteristics. Results: Interleaved acquisition of two nuclei did not show any relevant influence on image quality (SNR of 13.0 for interleaved versus 13.2 for standard 23Na MRI and 176.4 for interleaved versus 178.0 for standard 1H MRI). The applied motion correction increased the consistency between two consecutive scans for all examined volunteers and improved the image quality for all kinds of motion. The SD of the differences ranged between 2.30% and 6.96% for the uncorrected and between 2.13% and 2.67% for the corrected images. Conclusion: The feasibility of interleaved acquired 1H navigator images to be used for retrospective motion correction of 23Na images was successfully demonstrated. The approach neither affected the 23Na image quality nor elongated the scan time and can therefore be an important tool to improve the accuracy of quantitative 23Na MRI.
CRIS-Team Scopus Importer:2022-04-15
Keywords: 23Na MRI; 7 Tesla; brain MRI; interleaved dual-nuclear MRI; motion correction; ultrahigh field strength

MRI of Potassium and Sodium Enables Comprehensive Analysis of Ion Perturbations in Skeletal Muscle Tissue After Eccentric Exercise. - Gast, Lena; Baier, Laura Marie; Meixner, Christian; Chaudry, Oliver; Engelke, Klaus; Uder, Michael; Nagel, Armin Michael; Heiß, Rafael (Investigative Radiology, 2023)
OBJECTIVES: The aims were to investigate if potassium ( 39 K) magnetic resonance imaging (MRI) can be used to analyze changes in the apparent tissue potassium concentration (aTPC) in calf muscle tissue after eccentric exercise and in delayed-onset muscle soreness, and to compare these to corresponding changes in the apparent tissue sodium concentration (aTSC) measured with sodium ( 23 Na) MRI. MATERIALS AND METHODS: Fourteen healthy subjects (7 female, 7 male; 25.0 ± 2.8 years) underwent 39 K and 23 Na MRI at a 7 T MR system, as well as 1 H MRI at a 3 T MR system. Magnetic resonance imaging data and blood samples were collected at baseline (t0), directly after performing eccentric exercise (t1) and 48 hours after exercise (t2). Self-reported muscle soreness was evaluated using a 10-cm visual analog scale for pain (0, no pain; 10, worst pain) at t0, t1, and t2. Quantification of aTPC/aTSC was performed after correcting the measured 39 K/ 23 Na signal intensities for partial volume and relaxation effects using 5 external reference phantoms. Edema volume and 1 H T 2 relaxation times were determined based on the 1 H MRI data. Participants were divided according to their increase in creatine kinase (CK) level into high (CK t2 ≥ 10·CK t0 ) and low CK (CK t2 < 10·CK t0 ) subjects. RESULTS: Blood serum CK and edema volume were significantly increased 48 hours after exercise compared with baseline ( P < 0.001). Six participants showed a high increase in blood serum CK level at t2 relative to baseline, whereas 8 participants had only a low to moderate increase in blood serum CK. All participants reported increased muscle soreness both at rest and when climbing stairs at t1 (0.4 ± 0.7; 1.4 ± 1.2) and t2 (1.6 ± 1.4; 4.8 ± 1.9) compared with baseline (0 ± 0; 0 ± 0). Moreover, aTSC was increased at t1 in exercised muscles of all participants (increase by 57% ± 24% in high CK, 73% ± 33% in low CK subjects). Forty-eight hours after training, subjects with high increase in blood serum CK still showed highly increased aTSC (increase by 79% ± 57% compared with t0). In contrast, aTPC at t2 was elevated in exercised muscles of low CK subjects (increase by 19% ± 11% compared with t0), in which aTSC had returned to baseline or below. Overall, aTSC and aTPC showed inverse evolution, with changes in aTSC being approximately twice as high as in aTPC. CONCLUSIONS: Our results showed that 39 K MRI is able to detect changes in muscular potassium concentrations caused by eccentric exercise. In combination with 23 Na MRI, this enables a more holistic analysis of tissue ion concentration changes.
EVALuna2:520477

Multi-echo–based fat artifact correction for CEST MRI at 7 T - Tkotz, Katharina; Liebert, Andrzej; Gast, Lena; Zeiger, Paula; Uder, Michael; Zaiß, Moritz; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2024)
Purpose: CEST MRI is influenced by fat signal, which can reduce the apparent CEST contrast or lead to pseudo-CEST effects. Our goal was to develop a fat artifact correction based on multi-echo fat–water separation that functions stably for 7 T knee MRI data. Methods: Our proposed algorithm utilizes the full complex data and a phase demodulation with an off-resonance map estimation based on the Z-spectra prior to fat–water separation to achieve stable fat artifact correction. Our method was validated and compared to multi-echo–based methods originally proposed for 3 T by Bloch–McConnell simulations and phantom measurements. Moreover, the method was applied to in vivo 7 T knee MRI examinations and compared to Gaussian fat saturation and a published single-echo Z-spectrum–based fat artifact correction method. Results: Phase demodulation prior to fat–water separation reduced the occurrence of fat–water swaps. Utilizing the complex signal data led to more stable correction results than working with magnitude data, as was proposed for 3 T. Our approach reduced pseudo-nuclear Overhauser effects compared to the other correction methods. Thus, the mean asymmetry contrast at 3.5 ppm in cartilage over five volunteers increased from −9.2% (uncorrected) and −10.6% (Z-spectrum–based) to −1.5%. Results showed higher spatial stability than with the fat saturation pulse. Conclusion: Our work demonstrates the feasibility of multi-echo–based fat–water separation with an adaptive fat model for fat artifact correction for CEST MRI at 7 T. Our approach provided better fat artifact correction throughout the entire spectrum and image than the fat saturation pulse or Z-spectrum–based correction method for both phantom and knee imaging results.
CRIS-Team Scopus Importer:2023-12-08
Keywords: 7 T; CEST; fat artifact; fat–water separation; knee imaging; nuclear Overhauser effect

Muscle perfusion and the effect of compression garments in delayed-onset muscle soreness assessed with arterial spin labeling magnetic resonance imaging - Meixner, Christian; Nagel, Armin Michael; Höger, Svenja; Gast, Lena; Wiesmüller, Marco; Uder, Michael; May, Matthias; Hotfiel, Thilo; Heiß, Rafael (Quantitative Imaging in Medicine and Surgery, 2022)
Background: There is limited information about perfusion in exercise-induced muscle injuries such as delayed-onset muscle soreness (DOMS) and the effect of compression garments as a therapeutic strategy during the regeneration phase. The purpose of this prospective, explorative study was to evaluate muscle perfusion in DOMS and to assess the effect of compression garments at resting conditions and during DOMS by magnetic resonance (MR) arterial spin labeling (ASL). Methods: DOMS was induced from 03/2021 to 04/2021 using an eccentric and plyometric exercises targeting the calf muscles in 14 volunteers. A compression garment (21-22 mmHg) was worn during and for 6 h after exercise on one randomized leg. Magnetic resonance imaging (MRI) including ASL of both lower legs was performed before and directly after the exercise as well as after 6 h, and 48 h using a 3 Tesla MRI system. Perfusion analyses of the gastrocnemius muscle (GM) and the tibialis anterior muscle (TA) were performed and results were compared to baseline measurements. T2-weighted images and creatine kinase levels were acquired at baseline and after 48 h. Results: All volunteers presented a successful induction of DOMS in the GM after 48 h. Arterial muscle perfusion in the GM increased from baseline to measurements taken directly after the exercise (4.97 +/- 5.59 mL/100 g/min, P<0.001). No significant alteration in perfusion compared to baseline was observed at 6 h (P=0.16) and 48 h (P=1.0) after the induction of DOMS. Compression garments did not elicit a significant alteration in ASL parameters in the GM (P=0.65) or the TA (P=0.05) at any time point. No adverse events occurred during the study. Conclusions: After an initial exercise-associated increase in arterial muscle perfusion, a normalization of blood supply was observed at 6 and 48 h after the exercise intervention inducing DOMS. Wearing a compression garment (21-22 mmHg) during and after the induction of DOMS did not affect muscle perfusion at rest, nor did it have any significant effect on muscle perfusion during the regeneration phase. The results can help to better understand the pathophysiological properties of DOMS and may have implications for diagnostic and therapeutic strategies.
CRIS-Team WoS Importer:2022-08-05

Parameter optimization for proton density fat fraction quantification in skeletal muscle tissue at 7 T - Tkotz, Katharina; Zeiger, Paula; Hanspach, Jannis; Mathy, Claudius; Laun, Frederik Bernd; Uder, Michael; Nagel, Armin Michael; Gast, Lena (Magnetic Resonance Materials in Physics Biology and Medicine, 2024)
Objective: To establish an image acquisition and post-processing workflow for the determination of the proton density fat fraction (PDFF) in calf muscle tissue at 7 T. Materials and methods: Echo times (TEs) of the applied vendor-provided multi-echo gradient echo sequence were optimized based on simulations of the effective number of signal averages (NSA*). The resulting parameters were validated by measurements in phantom and in healthy calf muscle tissue (n = 12). Additionally, methods to reduce phase errors arising at 7 T were evaluated. Finally, PDFF values measured at 7 T in calf muscle tissue of healthy subjects (n = 9) and patients with fatty replacement of muscle tissue (n = 3) were compared to 3 T results. Results: Simulations, phantom and in vivo measurements showed the importance of using optimized TEs for the fat–water separation at 7 T. Fat–water swaps could be mitigated using a phase demodulation with an additional B0 map, or by shifting the TEs to longer values. Muscular PDFF values measured at 7 T were comparable to measurements at 3 T in both healthy subjects and patients with increased fatty replacement. Conclusion: PDFF determination in calf muscle tissue is feasible at 7 T using a chemical shift-based approach with optimized acquisition and post-processing parameters.
CRIS-Team Scopus Importer:2024-08-16
Keywords: 7 Tesla; Dixon MRI; Fat–water separation (FWS); Proton density fat fraction (PDFF); Skeletal muscle tissue

Quantification of Sodium Relaxation Times and Concentrations as Surrogates of Proteoglycan Content of Patellar CARTILAGE at 3T MRI - Kamp, Benedikt; Frenken, Miriam; Henke, Jan M.; Abrar, Daniel B.; Nagel, Armin Michael; Gast, Lena; Oeltzschner, Georg; Wilms, Lena M.; Nebelung, Sven; Antoch, Gerald; Wittsack, Hans-Joerg; Mueller-Lutz, Anja (Diagnostics, 2021)
Sodium MRI has the potential to depict cartilage health accurately, but synovial fluid can influence the estimation of sodium parameters of cartilage. Therefore, this study aimed to reduce the impact of synovial fluid to render the quantitative compositional analyses of cartilage tissue technically more robust. Two dedicated protocols were applied for determining sodium T-1 and T-2* relaxation times. For each protocol, data were acquired from 10 healthy volunteers and one patient with patellar cartilage damage. Data recorded with multiple repetition times for T-1 measurement and multi-echo data acquired with an additional inversion recovery pulse for T-2* measurement were analysed using biexponential models to differentiate longitudinal relaxation components of cartilage (T-1,T-car) and synovial fluid (T-1,T-syn), and short (T-2s*) from long (T-2l*) transversal relaxation components. Sodium relaxation times and concentration estimates in patellar cartilage were successfully determined: T-1,T-car = 14.5 & PLUSMN; 0.7 ms; T-1,T-syn = 37.9 & PLUSMN; 2.9 ms; c(T-1-protocol) = 200 & PLUSMN; 48 mmol/L; T-2s* = 0.4 & PLUSMN; 0.1 ms; T-2l* = 12.6 & PLUSMN; 0.7 ms; c(T-2*-protocol) = 215 & PLUSMN; 44 mmol/L for healthy volunteers. In conclusion, a robust determination of sodium relaxation times is possible at a clinical field strength of 3T to quantify sodium concentrations, which might be a valuable tool to determine cartilage health.
CRIS-Team WoS Importer:2022-01-14

Quantitative 1H and 23Na muscle MRI in Facioscapulohumeral muscular dystrophy patients - Gerhalter, Teresa; Marty, Benjamin; Gast, Lena; Porzelt, Katharina; Heiß, Rafael; Uder, Michael; Schwab, Stefan; Carlier, Pierre G.; Nagel, Armin Michael; Türk, Matthias (Journal of Neurology, 2020)
Objective: Our aim was to assess the role of quantitative 1H and 23Na MRI methods in providing imaging biomarkers of disease activity and severity in patients with Facioscapulohumeral muscular dystrophy (FSHD). Methods: We imaged the lower leg muscles of 19 FSHD patients and 12 controls with a multimodal MRI protocol to obtain STIR-T2w images, fat fraction (FF), water T2 (wT2), water T1 (wT1), tissue sodium concentration (TSC), and intracellular-weighted sodium signal (inversion recovery (IR) and triple quantum filter (TQF) sequence). In addition, the FSHD patients underwent muscle strength testing. Results: Imaging biomarkers related with water mobility (wT1 and wT2) and ion homeostasis (TSC, IR, TQF) were increased in muscles of FSHD patients. Muscle groups with FF > 10% had higher wT2, wT1, TSC, IR, and TQF values than muscles with FF < 10%. Muscles with FF < 10% resembled muscles of healthy controls for these MRI disease activity measures. However, wT1 was increased in few muscles without fat replacement. Furthermore, few STIR-negative muscles (n = 11/76) exhibited increased wT1, TSC, IR or TQF. Increased wT1 as well as 23Na signals were also present in muscles with normal wT2. Muscle strength was related to the mean FF and all imaging biomarkers of tibialis anterior except wT2 were correlated with dorsal flexion. Conclusion: The newly evaluated imaging biomarkers related with water mobility (wT1) and ion homeostasis (TSC, IR, TQF) showed different patterns compared to the established markers like FF in muscles of FSHD patients. These quantitative biomarkers could thus contain valuable complementary information for the early characterization of disease progression.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Facioscapulohumeral muscular dystrophy; Quantitative MRI; Sodium MRI; Triple quantum filter; Water T

Quantitative 7T sodium magnetic resonance imaging of the human brain using a 32-channel phased-array head coil: Application to patients with secondary progressive multiple sclerosis - Wilferth, Tobias; Mennecke, Angelika; Gast, Lena; Lachner, Sebastian; Müller, Max; Rothhammer, Veit; Huhn, Konstantin; Uder, Michael; Dörfler, Arnd; Nagel, Armin Michael; Schmidt, Manuel (NMR in Biomedicine, 2022)
Apparent tissue sodium concentrations (aTSCs) determined by 23Na brain magnetic resonance imaging (MRI) have the potential to serve as a biomarker in pathologies such as multiple sclerosis (MS). However, the quantification is hindered by the intrinsically low signal-to-noise ratio of 23Na MRI. The purpose of this study was to improve the accuracy and reliability of quantitative 23Na brain MRI by implementing a dedicated postprocessing pipeline and to evaluate the applicability of the developed approach for the examination of MS patients. 23Na brain MRI measurements of 13 healthy volunteers and 17 patients with secondary progressive multiple sclerosis (SPMS) were performed at 7 T using a dual-tuned 23Na/1H birdcage coil with a receive-only 32-channel phased array. The aTSC values were determined for normal appearing white matter (NAWM) and normal appearing gray matter (NAGM) in healthy subjects and SPMS patients. Signal intensities were normalized using the mean cerebrospinal fluid (CSF) sodium concentration determined in 37 separate patients receiving a spinal tap for routine diagnostic purposes. Five volunteers underwent MRI examinations three times in a row to assess repeatability. Coefficients of variation (CoVs) were used to quantify the repeatability of the proposed method. aTSC values were compared regarding brain regions and subject cohort using the paired-samples Wilcoxon rank-sum test. Laboratory CSF sodium concentration did not differ significantly between patients without and with MS (p = 0.42). The proposed quantification workflow for 23Na MRI was highly repeatable with CoVs averaged over all five volunteers of 1.9% ± 0.9% for NAWM and 2.2% ± 1.6% for NAGM. Average NAWM aTSC was significantly higher in patients with SPMS compared with the control group (p = 0.009). Average NAGM aTSC did not differ significantly between healthy volunteers and MS patients (p = 0.98). The proposed postprocessing pipeline shows high repeatability and the results can serve as a baseline for further studies establishing 23Na brain MRI as a biomarker in diseases such as MS.
CRIS-Team Scopus Importer:2022-08-19
Keywords: 7 T; brain MRI; multiple sclerosis

Recent technical developments and clinical research applications of sodium (23Na) MRI - Gast, Lena; Platt, Tanja; Nagel, Armin Michael; Gerhalter, Teresa (Progress in Nuclear Magnetic Resonance Spectroscopy, 2023)
Sodium is an essential ion that plays a central role in many physiological processes including the transmembrane electrochemical gradient and the maintenance of the body's homeostasis. Due to the crucial role of sodium in the human body, the sodium nucleus is a promising candidate for non-invasively assessing (patho-)physiological changes. Almost 10 years ago, Madelin et al. provided a comprehensive review of methods and applications of sodium (23Na) MRI (Madelin et al., 2014) [1]. More recent review articles have focused mainly on specific applications of 23Na MRI. For example, several articles covered 23Na MRI applications for diseases such as osteoarthritis (Zbyn et al., 2016, Zaric et al., 2020) [2,3], multiple sclerosis (Petracca et al., 2016, Huhn et al., 2019) [4,5] and brain tumors (Schepkin, 2016) [6], or for imaging certain organs such as the kidneys (Zollner et al., 2016) [7], the brain (Shah et al., 2016, Thulborn et al., 2018) [8,9], and the heart (Bottomley, 2016) [10]. Other articles have reviewed technical developments such as radiofrequency (RF) coils for 23Na MRI (Wiggins et al., 2016, Bangerter et al., 2016) [11,12], pulse sequences (Konstandin et al., 2014) [13], image reconstruction methods (Chen et al., 2021) [14], and interleaved/simultaneous imaging techniques (Lopez Kolkovsky et al., 2022) [15]. In addition, 23Na MRI topics have been covered in review articles with broader topics such as multinuclear MRI or ultra-high-field MRI (Niesporek et al., 2019, Hu et al., 2019, Ladd et al., 2018) [16–18]. During the past decade, various research groups have continued working on technical improvements to sodium MRI and have investigated its potential to serve as a diagnostic and prognostic tool. Clinical research applications of 23Na MRI have covered a broad spectrum of diseases, mainly focusing on the brain, cartilage, and skeletal muscle (see Fig. 1). In this article, we aim to provide a comprehensive summary of methodological and hardware developments, as well as a review of various clinical research applications of sodium (23Na) MRI in the last decade (i.e., published from the beginning of 2013 to the end of 2022).
CRIS-Team Scopus Importer:2023-06-09
Keywords: Multinuclear MRI; Sodium (; Sodium ions (Na; Tissue sodium concentration (TSC); X-nuclei imaging

Relaxation-weighted Na-23 magnetic resonance imaging maps regional patterns of abnormal sodium concentrations in amyotrophic lateral sclerosis - Mueller, Hans-Peter; Nagel, Armin Michael; Keidel, Franziska; Wunderlich, Arthur; Hubers, Annemarie; Gast, Lena; Ludolph, Albert C.; Beer, Meinrad; Kassubek, Jan (Therapeutic Advances in Chronic Disease, 2022)
Objectives: Multiparametric magnetic resonance imaging (MRI) is established as a technical instrument for the characterisation of patients with amyotrophic lateral sclerosis (ALS). The contribution of relaxation-weighted sodium ((NaR)-Na-23) MRI remains to be defined. The aim of this study is to apply (NaR)-Na-23 MRI to investigate brain sodium homeostasis and map potential alterations in patients with ALS as compared with healthy controls.
CRIS-Team WoS Importer:2022-07-29

Sodium and quantitative hydrogen parameter changes in muscle tissue after eccentric exercise and in delayed-onset muscle soreness assessed with magnetic resonance imaging - Höger, Svenja; Gast, Lena; Marty, Benjamin; Hotfiel, Thilo; Bickelhaupt, Sebastian; Uder, Michael; Heiß, Rafael; Nagel, Armin Michael (NMR in Biomedicine, 2022)
The objective of the current study was to assess sodium (Na-23) and quantitative proton (H-1) parameter changes in muscle tissue with magnetic resonance imaging (MRI) after eccentric exercise and in delayed-onset muscle soreness (DOMS). Fourteen participants (mean age: 25 +/- 4 years) underwent Na-23/H-1 MRI of the calf muscle on a 3-T MRI system before exercise (t0), directly after eccentric exercise (t1), and 48 h postintervention (t2). In addition to tissue sodium concentration (TSC), intracellular-weighted sodium (ICwS) signal was acquired using a three-dimensional density-adapted radial projection readout with an additional inversion recovery preparation module. Phantoms containing saline solution served as references to quantify sodium concentrations. The H-1 MRI protocol consisted of a T-1-weighted turbo spin echo sequence, a T-2-weighted turbo inversion recovery, as well as water T-2 mapping and water T-1 mapping. Additionally, blood serum creatine kinase (CK) levels were assessed at baseline and 48 h after exercise. The TSC and ICwS of exercised muscles increased significantly from t0 to t1 and decreased significantly from t1 to t2. In the soleus muscle (SM), ICwS decreased below baseline values at t2. In the tibialis anterior muscle (TA), TSC and ICwS remained at baseline levels at each measurement point. However, high-CK participants (i.e., participants with a more than 10-fold CK increase, n = 3) displayed different behavior, with 2- to 4-fold increases in TSC values in the medial gastrocnemius muscle (MGM) at t2. H-1 water T-1 relaxation times increased significantly after 48 h in the MGM and SM. H-1 water T-2 relaxation times and muscle volume increased in the MGM at t2. Sodium MRI parameters and water relaxation times peaked at different points. Whereas water relaxation times were highest at t2, sodium MRI parameters had already returned to baseline values (or even below baseline values, for low-CK participants) by this point. The observed changes in ion concentrations and water relaxation time parameters could enable a better understanding of the physiological processes during DOMS and muscle regeneration. In the future, this might help to optimize training and to reduce associated sports injuries.
CRIS-Team WoS Importer:2022-11-25

Sodium quantification in skeletal muscle: comparison between Cartesian gradient-echo and radial ultra-short echo time 23Na MRI techniques - Gerhalter, Teresa; Schilling, Felix; Zeitouni, Nour; Linz, Peter; Baudin, Pierre Yves; Kannenkeril, Dennis; Kopp, Christoph; Dahlmann, Anke; Schmieder, Roland; Uder, Michael; Nagel, Armin Michael; Gast, Lena (European Radiology Experimental, 2024)
Background: Clinical magnetic resonance imaging (MRI) studies often use Cartesian gradient-echo (GRE) sequences with 2-ms echo times (TEs) to monitor apparent total sodium concentration (aTSC). We compared Cartesian GRE and ultra-short echo time three-dimensional (3D) radial-readout sequences for measuring skeletal muscle aTSC. Methods: We retrospectively evaluated 211 datasets from 112 volunteers aged 62.3 ± 12.1 years (mean ± standard deviation), acquired at 3 T from the lower leg. For 23Na MRI acquisitions, we used a two-dimensional Cartesian GRE sequence and a density-adapted 3D radial readout sequence with cuboid field-of-view (DA-3D-RAD-C). We calibrated the 23Na MR signal using reference tubes either with or without agarose and subsequently performed a relaxation correction. Additionally, we employed a six-echo 1H GRE sequence and a multi-echo spin-echo sequence to calculate proton density fat fraction (PDFF) and water T2. Paired Wilcoxon signed-rank test, Cohen dz for paired samples, and Spearman correlation were used. Results: Relaxation correction effectively reduced the differences in muscle aTSC between the two acquisition and calibration methods (DA-3D-RAD-C using NaCl/agarose references: 20.05 versus 19.14 mM; dz = 0.395; Cartesian GRE using NaCl/agarose references: 19.50 versus 18.82 mM; dz = 0.427). Both aTSC of the DA-3D-RAD-C and Cartesian GRE acquisitions showed a small but significant correlation with PDFF as well as with water T2. Conclusions: Different 23Na MRI acquisition and calibration approaches affect aTSC values. Applying relaxation correction is advised to minimize the impact of sequence parameters on quantification, and considering additional fat correction is advisable for patients with increased fat fractions. Relevance statement: This study highlights relaxation correction’s role in improving sodium MRI accuracy, paving the way for better disease assessment and comparability of measured sodium signal in patients. Key points: • Differences in MRI acquisition methods hamper the comparability of sodium MRI measurements. • Measured sodium values depend on used MRI sequences and calibration method. • Relaxation correction during postprocessing mitigates these discrepancies. • Thus, relaxation correction enhances accuracy of sodium MRI, aiding its clinical use. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-05-31
Keywords: Calibration; Magnetic resonance imaging; Muscle (skeletal); Sodium; Volunteers

T-2* Accelerated quantification of tissue sodium concentration in skeletal muscle tissue: quantitative capability of dictionary learning compressed sensing - Utzschneider, Matthias; Behl, Nicolas G. R.; Lachner, Sebastian; Gast, Lena; Maier, Andreas; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance Materials in Physics Biology and Medicine, 2020)
OBJECTIVE: To accelerate tissue sodium concentration (TSC) quantification of skeletal muscle using 23Na MRI and 3D dictionary-learning compressed sensing (3D-DLCS). MATERIALS AND METHODS: Simulations and in vivo 23Na MRI examinations of calf muscle were performed with a nominal spatial resolution of [Formula: see text]. Fully sampled and three undersampled 23Na MRI data sets (undersampling factors (USF) = 3, 4.4, 6.7) were evaluated. Ten healthy subjects were examined on a 3 Tesla MRI system. Results of the simulation study and the in vivo measurements were compared to the ground truth (GT) and the fully sampled fast Fourier transform (NUFFT) reconstruction, respectively. RESULTS: Reconstruction results of simulated data with optimized 3D-DLCS yielded a lower deviation (< 4%) from the GT than results of the NUFFT reconstruction (> 5%) and a lower standard deviation (SD). For in vivo measurements, a TSC of [Formula: see text] was observed. The mean deviation from the reference is lower for the undersampled 3D-DLCS reconstructions (3.4%) than for NUFFT reconstructions (4.6%). SD is reduced using 3D-DLCS. Compared to a fully sampled NUFFT reconstruction, acquisition time could be reduced by a factor of 4.4 while maintaining similar quantitative accuracy. DISCUSSION: The optimized 3D-DLCS reconstruction enables accelerated TSC measurements with high quantification accuracy.
CRIS-Team WoS Importer:2020-01-31

Towards accelerated quantitative sodium MRI at 7 T in the skeletal muscle: Comparison of anisotropic acquisition- and compressed sensing techniques - Utzschneider, Matthias; Müller, Max; Gast, Lena; Lachner, Sebastian; Behl, Nicolas G.R.; Maier, Andreas; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance Imaging, 2021)
Purpose: To compare three anisotropic acquisition schemes and three compressed sensing (CS) approaches for accelerated tissue sodium concentration (TSC) quantification using 23Na MRI at 7 T. Materials and methods: Three anisotropic 3D-radial acquisition sequences were evaluated using simulations, phantom- and in vivo TSC measurements: An anisotropic density-adapted 3D-radial sequence (3DPR-C), a 3D acquisition-weighted density-adapted stack-of-stars sampling scheme (SOS) and a SOS approach with golden-ratio rotation (SOS-GR). Eight healthy volunteers were examined at a 7 Tesla MRI system. TSC measurements of the calf were conducted with a nominal spatial resolution of Δx = (3.0 × 3.0 × 15.0) mm3 and a field of view of (156.0 × 156.0 × 240.0) mm3 for multiple undersampling factors (USF). Three CS reconstructions were evaluated: Total variation CS (TV-CS), 3D dictionary-learning compressed sensing (3D-DLCS) and TV-CS with a block matching prior (TV-BL-CS). Results of the simulations and measurements were compared to a simulated ground truth (GT) or a fully sampled reference measurement (FS), respectively. The deviation of the mean TSC evaluated in multiple ROI (mEGT/FS) and the normalized root-mean-squared error (NRMSE) for simulations were evaluated for CS and NUFFT reconstructions. Results: In simulations, the SOS-GR yielded the lowest NRMSE and mEGT (< 4%) with NUFFT for an acquisition time (TA) of less than 2 min. CS further improved the results. In simulations and measurements, the best TSC quantification results were obtained with 3D-DLCS and SOS-GR (lowest NRMSE, mEGT < 2.6% in simulations, mEGT < 10.7% for phantom measurements and mEFS < 6% in vivo) with an USF = 4.1 (TA < 2 min). TV-CS showed no or only slight improvements to NUFFT. The results of TV-BL-CS were similar to 3D-DLCS. Discussion: The TA for TSC measurements could be reduced to less than 2 min by using adapted sequences such as SOS-GR and CS reconstruction approaches such as 3D-DLCS or TV-BL-CS, while the quantitative accuracy stays comparable to a fully sampled NUFFT reconstruction (approx. 8 min TA). In future, the lower TA could improve clinical applicability of TSC measurements.
CRIS-Team Scopus Importer:2020-11-06
Keywords: 7 tesla; Anisotropic acquisition schemes; Compressed sensing; Image reconstruction; Skeletal muscle; Sodium (